CERVICAL SPINAL INJURIES IN MODERATE TO SEVERE HEAD INJURIES - Nazir, Muhammad; Khan, Shahbaz Ali; Raja, Riaz A; Bhatti, Sajid Nazir; Ahmed, Ehtisham (Journal of Ayub Medical College Abbottabad, 2012)
Background: Traumatic Brain Injury (TBI) is the leading cause of death in all age group. The incidence of CSI increases with the severity of TBI so prompt care of cervical spine is necessary in all patients with moderate to severe head injury. The objective of this study was to determine the frequency of cervical injury in patients with moderate to severe head injury and different types of trauma. Methods: This descriptive cross sectional study was conducted in department of Neurosurgery Ayub Medical College, Abbottabad from October 2011 to October 2012. A total of 369 patients were included in this study by consecutive (non probability) sampling. All patients were subjected to X-rays and CT-Scan of the skull for evaluation of head injury. X-rays and CT scan with MRI of cervical spine were done for evaluation of cervical spinal injury. Results: A total of 369 patients were included in our study, out of which 276 (74.8%) were males and 93 (25.2%) were females. Age of the patients ranged from 3-90 years with mean of 31.93±21.35. Among these patients most common cause of injury was fall 196 (53.1%), whereas the RTA was 159 (43.1%) and assault was 14 (3.8%). Out of the 369 patients 42 (11.3%) were found to have cervical spinal injuries. Conclusion: The frequency of cervical injury associated with moderate to severe head injury remains the same in all over the world with minor difference in percentages; that we have observed in our study. Furthermore, we have observed that cervical injury is directly proportional to the severity of head injury. All the head injured patients should be suspected of having cervical spinal injury unless proved otherwise. Keywords: spinal injury, cervical injury, head injury.